2023
DOI: 10.3390/bioengineering10040484
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucosidase and Its Application in Bioconversion of Ginsenosides in Panax ginseng

Abstract: Ginsenosides are a group of bioactive compounds isolated from Panax ginseng. Conventional major ginsenosides have a long history of use in traditional medicine for both illness prevention and therapy. Bioconversion processes have the potential to create new and valuable products in pharmaceutical and biological activities, making them both critical for research and highly economic to implement. This has led to an increase in the number of studies that use major ginsenosides as a precursor to generate minor one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Palaniyandi et al [ 9 ] showed that Rb 1 /Rb 2 glycol saponins are transformed by microorganisms to generate Rd, and Rd can then be further converted to Rg 3 , Rh 2 , F 2 , and CK. Bai [ 46 ] and Tran [ 47 ] speculated that the conversion pathways of the diol ginsenosides are Rb 1 /Rb 2 → Rd→Rg 3 → Rh 2 , Rb 1 /Rc → Rd → Rg 1 , Rg 3 → Rg 5 + Rk 1 , and Rb 1 → Rd → F 2 → Rg 3 → CK, while the triol ginsenoside conversion pathway is Re → Rg 1 → Rh 1 → Rh 4 → PPT.…”
Section: Resultsmentioning
confidence: 99%
“…Palaniyandi et al [ 9 ] showed that Rb 1 /Rb 2 glycol saponins are transformed by microorganisms to generate Rd, and Rd can then be further converted to Rg 3 , Rh 2 , F 2 , and CK. Bai [ 46 ] and Tran [ 47 ] speculated that the conversion pathways of the diol ginsenosides are Rb 1 /Rb 2 → Rd→Rg 3 → Rh 2 , Rb 1 /Rc → Rd → Rg 1 , Rg 3 → Rg 5 + Rk 1 , and Rb 1 → Rd → F 2 → Rg 3 → CK, while the triol ginsenoside conversion pathway is Re → Rg 1 → Rh 1 → Rh 4 → PPT.…”
Section: Resultsmentioning
confidence: 99%
“…The bioconversion of ginsenoside Rb1 to CK via β-glu is an effective production method in industry [ 50 ]. Microbes isolated from the soils of ginseng farms, soybeans, tea, the gastrointestinal tract of humans, kimchi, and other fermented items can be a source of β-glu [ 51 ]. Heat-resistant β-glu yields the highest amount of CK from protopanaxadiol-type ginsenosides [ 52 ].…”
Section: Biotransformation Of Ckmentioning
confidence: 99%
“…We included the manually curated ginsenoside conversion microbial enzymes [27] and enzymes involved in the ginsenoside biosynthesis pathway from MetaCyc database [28], along with nine genome proteomes. Moreover, we obtained the KEGG secondary metabolite pathways from KEGG pathway database (https://www.genome.jp/kegg/pathway.…”
Section: Clustering Of Proteomementioning
confidence: 99%